Low-Voltage, Flexible, and Self-Encapsulated Ultracompact Organic Thin-Film Transistors Based on Nanomembranes - Torikai, Kleyton [UNESP]; Furlan De Oliveira, Rafael; Starnini De Camargo, Davi H. [UNESP]; Bof Bufon, Carlos C. [UNESP] (American Chemical Society (ACS), 2018)
Organic thin-film transistors (OTFTs) are an ever-growing subject of research, powering recent technologies such as flexible and wearable electronics. Currently, many studies are being carried out to push forward the state-of-the-art OTFT technology to achieve characteristics that include high carrier mobility, low power consumption, flexibility, and the ability to operate under harsh conditions. Here, we tackle this task by proposing a novel OTFT architecture exploring the so-called rolled-up nanomembrane technology to fabricate low-voltage (<2 V), ultracompact OTFTs. As the OTFT gate electrode, we use strained nanomembranes, which allows all transistor components to be rolled-up and confined into a tubular-shaped tridimensional device structure with reduced footprint (ca. 90% of their planar counterpart), without any loss of electrical performance. Such an innovative architecture endows the OTFTs high mechanical flexibility (bending radius of <30 μm) and robustness - the devices can be reversibly deformed, withstanding more than 500 radial compression/decompression cycles. Additionally, the tubular device design possesses an inherent self-encapsulation characteristic that protects the OTFT active region from degradation by UV-light and hazardous vapors. The reported strategy is also shown to be compatible with different organic semiconductor materials. All of these characteristics contribute to further extending the potentialities of OTFTs, mainly toward rugged electronics.
Keywords: flexible electronics; Organic thin-film transistors (OTFTs); rugged electronics; strained nanomembranes; ultracompact devices